1993
DOI: 10.1111/j.1574-6968.1993.tb05980.x
|View full text |Cite
|
Sign up to set email alerts
|

A structural model for the GroEL chaperonin

Abstract: Individual particle analysis of end views from negatively stained specimens of purified GroEL from Escherichia coli showed the presence of two different particle populations, those with a six-fold symmetry and those with a seven-fold symmetry, when studied at pH 7.7 and 5.0. Image processing of particles from frozen-hydrated specimens revealed at both pH values a homogeneous population of particles with a strong seven-fold symmetry component and an average image with seven asymmetric units. Biochemical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The presumptive relationship between Asp60 and Hsp62 will require further definition. Modified forms of GroEL appear in Escherichia coli during the heat shock response and, following prolonged storage, exhibit retarded migration in SDS-PAGE and an increasingly acidic isoelectric point on twodimensional gels (29,41). Preliminary Southern blot analysis (data not shown) has ruled out the possibility that Asp60 represents the product of a related gene, as observed for Mycobacterium spp., streptomycetes, and Synechocystis spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presumptive relationship between Asp60 and Hsp62 will require further definition. Modified forms of GroEL appear in Escherichia coli during the heat shock response and, following prolonged storage, exhibit retarded migration in SDS-PAGE and an increasingly acidic isoelectric point on twodimensional gels (29,41). Preliminary Southern blot analysis (data not shown) has ruled out the possibility that Asp60 represents the product of a related gene, as observed for Mycobacterium spp., streptomycetes, and Synechocystis spp.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple forms with various isoelectric points are also apparent in the IEF dimension and are similar to the forms observed with Hsp62, albeit slightly more basic. Additional experiments are necessary to confirm the identity of this gene product and to determine whether Asp60 represents an unrelated protein, the product of a related gene (18,24,26,38), or a modified version (posttranslational modification) of Hsp62 (11,29,41). (10).…”
Section: Sds-page Analysis Of B Abortus Protein Synthesis In Responsmentioning
confidence: 99%
“…Micrographs were digitized using a Eikonix IEEE-488 camera with a sampling window corresponding to 4.7 A/pixel. Image processing of individual particles was carried out as described by Carrascosa et al (1990), except that average images were calculated using an improved alignment algorithm (Penczek et al, 1992;Marco et al, 1993). In the case of actin binary complex preparations, particles having a central stain-filled domain were separated from those showing a stain-penetrating central region using a Kohonen-based self-organizing map classifier (Kohonen, 1990;Marabini and Carazo, 1994).…”
Section: Electron Microscopy and Image Processingmentioning
confidence: 99%
“…Neurodegenerative disorders may be a consequence of proteostasis deficiency, while cancer could result from enhanced proteostasis capacity ( Powers et al, 2009 ). Key structural studies of molecular chaperones in the 1990s ( Marco et al, 1993 ) revealed these as essential components of the network governing protein homeostasis. Though in vitro studies revealed much on the basic principles of protein folding, how proteins fold in the crowded in vivo cellular environment remains to be fully understood.…”
Section: Introductionmentioning
confidence: 99%